PERAN PALANG MERAH INDONESIA (PMI) DALAM PEMBEBASAN SANDERA WARGA NEGARA INDONESIA (WNI) OLEH KELOMPOK TERORIS ABU SAYYAF PADA TAHUN 2016 - Tholhah Tholhah; Anggun Dwi Panorama; Winda Nur Janah (Universitas Jenderal Ahmad Yani, 2023)
In 2016, kidnappings at sea globally experienced an increase in cases compared to the previous 10 years. One of them occurred in the Sulu Sea which is between eastern Malaysia and the Philippines. A series of kidnappings for ransom have been reported since March 2016. As of 2016, there have been 17 kidnapping cases at sea and 6 failed abduction attempts at sea, of which some of the victims came from Indonesia. The kidnappings are related to attacks carried out by a terrorist group operating in the Southern Philippines, namely the Abu Sayyaf terrorist group. This study aims to analyze the role of the Indonesian Red Cross (PMI) as a non-state actor in negotiating with the Abu Sayyaf group to free 10 Indonesian citizens (WNI) who were taken as hostages on March 26 2016. The author uses a sociological liberalism theory approach, the concept of track two diplomacy and negotiation according to Guy Olivier Faure which consists of three stages of negotiation, namely (1) the pre-negotiation stage, (2) the formula formation stage, and (3) the adjustment stage to analyze PMI's role. The results of this study indicate that PMI's role in the effort to free the 10 Indonesian citizens highlighted its role as a non-state actor who prioritized humanitarian assistance through the negotiation process so as to facilitate the release of the hostages which in the end the 10 Indonesian citizens were released on May 1, 2016.